0031 Sleep Regularity is Associated with DNA Methylation in Cognitive, Cardiovascular and Mood-related Genes: A GWAS-informed Study in Adolescents. (25th May 2022) - Larsen, Michael; Morales-Ghinaglia, Natasha; He, Fan; Imamura, Yuka; Berg, Arthur; Vgontzas, Alexandros; Liao, Duanping; Bixler, Edward; Fernandez-Mendoza, Julio
Abstract: Introduction: Adolescence is associated with a delay in the circadian timing of sleep. However, social factors prevent adolescents from adapting to a later sleep-wake pattern, leading to different forms of circadian misalignment that may increase the risk of cardiovascular and mental health disorders. Several GWAS have identified genes associated with sleep and circadian phenotypes, however, little is known regarding the epigenetic basis and significance of sleep timing and its regularity in adolescence. Methods: We analyzed data from 230 adolescents from the Penn State Child Cohort follow-up study who provided a blood sample for DNA extraction and had complete at-home 7-night (at least 3) actigraphy (ACT) data. ACT-measured sleep midpoint was calculated as the intra-individual mean of the 7-night midpoint (zeroed to midnight) of the sleep period. ACT-measured sleep regularity was calculated as the intra-individual standard deviation of the 7-night sleep midpoint. Epigenome-wide single nucleotide resolution of DNA methylation in cytosine-phosphate-guanine (CpG) sites and surrounding regions were obtained from peripheral leukocytes. This study focuses on methylation sites in GWAS-informed genes previously associated with sleep and circadian phenotypes. Linear regression assessed the association between sleep midpoint and sleep regularity with site-specific methylation levels, adjusting for sex, age, race/ethnicity, body mass index, and psychotropic medication use. Using the Benjamini & Hochberg method to adjust for a false discovery rate. Adjusted p-values are reported as q-values. Results: Sleep midpoint was not associated with a significant change in methylation at any of the measured intragenic sites. Sleep regularity was significantly associated with differential methylation at 238 intragenic sites in 147 genes with an adjusted p<0.05, of which, three sites were within GWAS-informed sleep/circadian-related genes. Higher sleep irregularity was associated with hypermethylation in MAD1L1 (q=2.4x10-2) and with hypomethylation in CALN1 (q=3.8 x 10-4) and ZNF618 (q=3.8 x 10-2). Conclusion: Sleep irregularity is associated with altered DNA methylation in genes previously identified in GWAS of sleep/circadian phenotypes. Our data provides evidence for a potential epigenetic link between sleep irregularity and genes involved in neurocognitive functioning (CALN1), internalizing disorders (MAD1L1) and blood pressure (ZNF618). Support (If Any): National Institutes of Health (R01HL136587, R01MH118308, UL1TR000127)